2007
DOI: 10.1016/j.jneumeth.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Micro-field evoked potentials recorded from the porcine sub-dural cortical surface utilizing a microelectrode array

Abstract: A sub-dural surface microelectrode array designed to detect microfield evoked potentials has been developed. The device is comprised of an array of 350-micron square gold contacts, with bidirectional spacing of 150 microns, contained within a polyimide Kapton material. Cytotoxicity testing suggests that the device is suitable for use with animal and human patients. Implementation of the device in animal studies revealed that reliable evoked potentials could be acquired. Further work will be needed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…It was reported that Kapton is a polyimide accepted for use in biomedical devices because of its proven biocompatibility . Primary human cortical cells were shown to adhere to Kapton for microelectrode applications . In our experiments, dramatically different responses from each tested cell line were obtained.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It was reported that Kapton is a polyimide accepted for use in biomedical devices because of its proven biocompatibility . Primary human cortical cells were shown to adhere to Kapton for microelectrode applications . In our experiments, dramatically different responses from each tested cell line were obtained.…”
Section: Resultsmentioning
confidence: 64%
“…26 Primary human cortical cells were shown to adhere to Kapton for microelectrode applications. 27 In our experiments, dramatically different responses from each tested cell line were obtained. Thus, normal human embryonic kidney cells (HEK 293T) contact inhibition seemed to be abrogated, while cells grew in multilayers covering the entire area of the BCZT-coated Kapton, as opposed to those grown on standard borosilicate cover glass.…”
Section: Resultsmentioning
confidence: 86%
“…The pitch between neighbored microelectrode sites is designed to be 400 μm, so that the 32-channel MEA can fit within a 3-mm-diameter circular surgery window. This level of electrode spacing is sufficient to capture the rich spatial information available and have been adopted for many previous studies ( 6 , 28 , 29 ). The scanning electron microscopy (SEM) image shown on the right of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Motor control signals 2 and spoken words 3 can be decoded with substantially improved performance utilizing electrodes spaced 1 mm apart or less. In occipital cortex, arrays with 500 μm spacing have demonstrated micro-field evoked potentials that can distinguish ocular dominance columns 4 . The spatial scale for some pathologic signals is also submillimeter, based on observations of microseizures, microdischarges and high frequency oscillations in epileptic brain 5 , 6 .…”
mentioning
confidence: 99%